2008
DOI: 10.1007/s00345-008-0283-y
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous nerve regeneration using acellular nerve grafts

Abstract: These findings show that the use of nerve guidance channel systems allow for accelerated and precise cavernosal nerve regeneration. Acellular nerve grafts represent a viable alternative to fresh autologous grafts in a rodent model of erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Furthermore, dynamically seeded corporal cells on acellular corporal tissue matrices and maintained in a bioreactor system resulted in improved formation of normal corpora (71% vs. 39% in statically seeded matrices) due to more dynamic cell attachment [86]. In addition to the engineered neo-corpora, cavernous nerve-excised rats, when implanted with acellular nerve grafts, demonstrated adequate ICP at 3 months and the presence of host-cell Adipose-derived stem cell Hypercholesterolemic rat ↑ ICP, nNOS, smooth muscle, and endothelial markers Huang et al [79] Adipose-derived stem cell CNI rat ↑ ICP, nNOS, and SMC preservation cGMP-cyclic guanosine monophosphate; CNI-cavernous nerve injury; eNOS-endothelial nitric oxide synthase; ICP-intracavernosal pressure; nNOS-neuronal nitric oxide synthase; NOS-nitric oxide synthase; SMC-smooth muscle cell infiltration within the nerve sheath [87]. These findings confirmed that the use of a nerve-guidance channel system allowed for accelerated and precise cavernosal nerve regeneration and represents a viable alternative to fresh autologous nerve graft in rodent models of ED.…”
Section: Tissue Engineeringmentioning
confidence: 98%
“…Furthermore, dynamically seeded corporal cells on acellular corporal tissue matrices and maintained in a bioreactor system resulted in improved formation of normal corpora (71% vs. 39% in statically seeded matrices) due to more dynamic cell attachment [86]. In addition to the engineered neo-corpora, cavernous nerve-excised rats, when implanted with acellular nerve grafts, demonstrated adequate ICP at 3 months and the presence of host-cell Adipose-derived stem cell Hypercholesterolemic rat ↑ ICP, nNOS, smooth muscle, and endothelial markers Huang et al [79] Adipose-derived stem cell CNI rat ↑ ICP, nNOS, and SMC preservation cGMP-cyclic guanosine monophosphate; CNI-cavernous nerve injury; eNOS-endothelial nitric oxide synthase; ICP-intracavernosal pressure; nNOS-neuronal nitric oxide synthase; NOS-nitric oxide synthase; SMC-smooth muscle cell infiltration within the nerve sheath [87]. These findings confirmed that the use of a nerve-guidance channel system allowed for accelerated and precise cavernosal nerve regeneration and represents a viable alternative to fresh autologous nerve graft in rodent models of ED.…”
Section: Tissue Engineeringmentioning
confidence: 98%
“…Therefore, methods of restoring nerve function in these patients are necessary. Different regenerative strategies used until now for repair or replacement of cavernous nerves include: use of silicone guidance tubes filled with primary Schwann cells, and nerve gap interposition with acellular nerve matrices, which showed significant nerve regeneration and ED recoverability [88]; use of sural nerve as a scaffold for cavernous nerve regeneration after radical prostatectomy, where partial improvement of ED and continence recovery were confirmed in many clinical studies [89][90][91][92][93]; and use of a nerve graft procedure after radical prostatectomy-a large clinical study in Japan indicated that this procedure might contribute to the recovery of urinary and sexual function [94].…”
Section: Penile Reconstructionmentioning
confidence: 99%
“…The core problem of transplantation immunity is the major histocompatibility complex(MHC), the expression product of MHC mainly exist at the surface of the cellular membrane, and compose the membrane antigen of cell, which is the main cause of transplantation immunity (22). Among the structural composition of peripheral nerve, the antigenicity of allogeneic nerve mainly exist at the schwann cell and medullary sheath, while the antigenicity of endoneurium, perineurium and epineurium which are all composed by collogen is very weak (3,10,16,19). The base plate of schwann cell (SCBL) is the basal membrane encasing the axis cylinder and schwann cell, it adheres the inner wall of each endoneurial tube of peripheral nerve, it is made up of extracellular matrix abundant with laminin, and it almost has no antigenicity.…”
Section: The Cytological Researchmentioning
confidence: 99%